2021
DOI: 10.1177/00307270211045410
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting strategies to incorporate gender-responsiveness into maize breeding in southern Africa

Abstract: In sub-Saharan Africa there is increasing focus on identifying women’s trait preferences within crop breeding to enable gender-responsive product development. In the case of maize, breeding programs are ready to incorporate specific traits to increase gender-responsiveness but lack guidance on what these specific traits might be. We propose an inductive approach to determine a pathway towards increasing gender-responsiveness within maize breeding. A survey of 306 farmers was conducted to determine gender diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…In Kenya, similarly, intensity of use of hybrid seed was lower among female-headed households, which used, on average, 1.8 kg less hybrid seed than male-headed households ( Smale and Olwande, 2014 ). Recent work in Zimbabwe documented differences in variety use among male and female plot managers ( Cairns et al, 2021b ), but clear explanations of these differences are still needed.…”
Section: Gender and Uptake Of Improved Maize Seedmentioning
confidence: 99%
See 2 more Smart Citations
“…In Kenya, similarly, intensity of use of hybrid seed was lower among female-headed households, which used, on average, 1.8 kg less hybrid seed than male-headed households ( Smale and Olwande, 2014 ). Recent work in Zimbabwe documented differences in variety use among male and female plot managers ( Cairns et al, 2021b ), but clear explanations of these differences are still needed.…”
Section: Gender and Uptake Of Improved Maize Seedmentioning
confidence: 99%
“…It rarely falls cleanly into either men's camp or women's and tends to be grown widely by both men- and women-headed households (e.g. Cairns et al, 2021b ; Doss, 2002 ). In East Africa, research has shown that responsibilities for its production are often shared between men and women, either in separate or jointly managed plots ( Adam et al, 2020a ; Adam et al, 2020b ).…”
Section: Gender-differentiated Variety Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, questions have been raised about the extent to which participatory approaches adequately reflect the wider conditions under which different social groups perform agricultural labour, their preferences beyond the (often production-related) traits already selected by the breeders, and their real-life decision-making and adoption behaviours, as well as the extent to which social and gender researchers are able to influence varietal design (e.g. Cernea and Kassam 2005;Ashby et al 2013;Almekinders et al 2019;Weltzien et al 2019;Cairns et al 2021;Voss et al 2021).…”
Section: The Rise Of Market-based Approaches To Demand-led and Gender...mentioning
confidence: 99%
“…Moreover, trait and varietal preferences may not fully predict adoption and buying behaviour (e.g. Cairns et al 2021) nor do they necessarily represent meaningful choices and may in several cases reflect "a self-subordinating adaptation to a restricted choice, to accommodate (…) inferior access to labor, capital, farm equipment, seed, fertilizers, pest control products and market access" (Polar et al 2021).…”
Section: The Gendered and More-than-human Marketplacementioning
confidence: 99%